Comparativo da presença do Mycobacterium Leprae entre mucosa nasal e o palato duro - Carvalho, Ricardo Sandri (2014)
Leprosy in Brazil is still endemic disease and the country ranks second in the world in absolute number of patients. Fighting it is public health priority, however, one of the biggest obstacles is undoubtedly of obtaining an early diagnosis of the patient and especially their household contacts. Mycobacterium leprae (M. leprae) is the causative agent of leprosy and its main route of transmission is done directly, most likely the respiratory tract. The bacillus can be found in the oral mucosa without showing any morphological change, and only the most sensitive laboratory methods to detect its presence. The objective of this research was to determine if the mucosa of the hard palate can be a place of importance in the early and reliable detection for the presence of M. leprae and the correlation of results obtained in nasal swab with shaved mucosa of the palate in seeking to contribute to the studies of prevention and control of disease, especially in newly diagnosed household contacts of patients. To this end, the method used was the technique of polymerase chain reaction quantitative (qPCR) and serological detection of antibodies specific phenolic glycolipid-1 (anti PGL-1) for M. leprae, performed by ELISA. The study included 78 patients with leprosy who had not started treatment (G1); its 54 household contacts (G2) and 80 individuals free of the disease for the negative control (G3). In results between the tests of collecting cells by nasal swabs and scraping the mucosa of the palate, it was found the presence of the bacillus in both sites (both G1 and G2) and demonstrated that the sensitivity of the exams qPCR RLEP are equivalent, with no statistically significant differences (positive in 35% of G1 in the mucosa of the hard palate and 44% for nasal, p = 0.3731 for G2 and 31% and 38%, respectively, p = 0, 6674). We conclude that the results can be considered relevant for the medical and dental field, enabling new strategies for early detection, prevention and treatments emerge. Thus, the oral cavity may be a route of infection and transmission of leprosy and household contacts may be actively involved in its transmission in highly endemic regions